DESIGN OF HOUSEHOLD ROBOTS: FUNCTIONAL AND AESTHETIC ASPECTS - Хоменко, Марія (SWorldJournal, 2026)
The article is devoted to the analysis of contemporary approaches to the design of domestic robots in the context of the rapid development of robotics and human-centered technologies. It examines the role of design as a key factor in integrating robots in